Molecular characterization by PCR-ITS technique of Fusarium oxysporum isolated from tomato in Baghdad city - Noor Saad Nahi Al-Adhami; Alaa Mohsen Al-Araji (Tikrit Journal of Pure Science)
The present study aimed to estimate the pathogenesis of Fusarium oxysporum isolates and identify them by molecular technique Polymerase Chain Reaction-Internal Transcript Spacer (PCR-ITS). A total of thirty Fusarium oxysporum isolates were isolated from infected tomato plants and diagnosed depending on 'morphological characteristics. The pathogenicity test was performed for thirty Fusarium oxysporum isolates. So it was procedure